Biomarkers, the control panel and personalized COPD medicine. Issue 1 (14th July 2015) - Agusti, Alvar; Gea, Joaquim; Faner, Rosa
Abstract: Chronic obstructive pulmonary disease (COPD) is a complex and heterogeneous disease, so its clinical management needs to be personalized as much as possible. 'Complex' means that COPD has several components with non‐linear dynamic interactions, whereas 'heterogeneous' indicates that not all these components are present in all patients or, in a given patient, at all time points. This complexity and heterogeneity explains and justifies the need for personalizing the assessment and treatment of patients with COPD. We propose here that the implementation of a ' control panel ' will facilitate the deployment of personalized COPD medicine in clinical practice. Such a control panel should provide the practicing clinician complementary and relevant information on treatable clinical characteristics in a single patient at a given time point. For the purpose of this discussion, we consider these variables to be ' biomarkers '. Which treatable clinical characteristics should the COPD control panel include has not yet been formally validated. The review below suggests and discusses which ones might be considered in the future and should be viewed as a working proposal.